Evaluasi Dosis Paparan Radiasi Pada Pemeriksaan MSCT Stonografi Kasus Urolithiasis Di Rumah Sakit Umum Pusat Dr. Hasan Sadikin Bandung. - Rahmat, Lili Julia; Oktarina Damayanti; Ardiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
Multislice Computed Tomography (MSCT) stenography is one of the preferred modalities for evaluating urolithiasis due to its high diagnostic accuracy. However, the increasing use of CT imaging has raised concerns regarding patient radiation exposure. This study aims to evaluate the radiation dose received by patients undergoing MSCT stenography at Dr. Hasan Sadikin General Hospital, Bandung, and to assess the influence of technical parameters on dose variability. This is a quantitative descriptive study using a cross-sectional approach. A total of 40 adult patients (male and female) who underwent MSCT stenography were selected as samples. Radiation dose data, including CTDIvol and DLP, were collected directly from the CT console and supported by patients’ medical records. Multiple linear regression analysis was performed to assess the relationship between CT dose and technical parameters such as kV, mAs, scan range, and volume of focus (VOF). The research showed that the average CTDIvol was 11.83 mGy and the average DLP was 644.64 mGy·cm, both of which exceeded the international Diagnostic Reference Levels (DRLs). Statistical analysis showed that only the mAs parameter had a significant effect on CTDIvol (p = 0.043), while other parameters such as kV, scan range, and VOF showed no significant influence.